QOLP-14. LONG-TERM IMPACT OF ADULT GLIOMA ON HEALTH-RELATED QUALITY OF LIFE: A SYSTEMATIC REVIEW. (12th November 2021) - Frances, Se Maria; Klein, Martin; Short, Susan; Murray, Louise; Velikova, Galina; Wright, Judy; Boele, Florien
Abstract: BACKGROUND: Glioma diagnosis can be devastating, and results in a wide range of symptoms. Relatively little is known about the long-term challenges these symptoms pose on HRQOL. The aim of this review is to identify the long-term HRQOL issues reported at least two years following diagnosis of glioma. METHOD: Systematic literature searches were carried out using Medline, EMBASE, CINAHL, PsycINFO, and Web of Science Core Collection. Searches were designed to identify a range of reported HRQOL aspects defined as physical, mental or social issues, in adult WHO grade II or III patients. To capture the full extent of patients' experience, studies of any design reporting on primary data where patients had at least two years follow-up from diagnosis were included. WHO grade I and grade IV tumours were excluded due to their different prognoses and the expected nature of their disease trajectories. Narrative synthesis was used to collate findings. RESULTS: The search returned 8438 articles. 477 titles remained after title and abstract screening, with seventeen full text articles included in the final analysis. The majority of studies used quantitative methods, with only two articles reporting qualitative or mixed methodology. Articles were predominantly cross-sectional studies (n = 9), along with cohort studies (n = 3), clinical trials (n = 3) and pilot studies (n = 2). Results indicated that patients reported a variety of issues influencing their HRQOL, with emotional/psychological/cognitive changes the most frequently reported. Physical complaints included problems with fatigue, seizures and maintaining daily activity. Social challenges included strained social relationships and issues managing finances. Patient coping strategies were found to significantly influence wellbeing and subsequent HRQOL. CONCLUSION: Glioma patients' long-term HRQOL and daily functioning can be impacted by their physical, mental and social wellbeing. Findings from this review lay the groundwork for efforts to improve patient long-term HRQOL.